DIAGNOSIS OF FUNGAL AND PARASITIC DERMATOPATHIES IN DOGS AND CATS OF PARAÍBA STATE, BRAZIL - VALENCIO, B. A.; VILELA, V. L. R.; FEITOSA, T. F.; SALES, I. C.; SILVA, S. S.; ARAÚJO, A. L. (Ars Veterinaria, 2018)
This study aimed to diagnose fungal and parasitic dermatopathies, describing its casuistry in dogs and cats at the Veterinary Hospital (VH) of the Instituto Federal da Paraíba (IFPB), Sousa, Paraíba. The study was carried out at the Laboratory of Immunology and Infectious Diseases (LIID) and at the Small Animal Medical Clinic (SAMC), VH/IFPB, Sousa, Paraíba, Brazil. Fifty-eight animals with skin lesions, including 41 dogs and 17 cats, were evaluated. Samples from the lesions were processed, resulting in 12.2% (5/41) of dogs testing positive for dermatophytes; 60% (3/5) of those cases were confirmed with Microsporum canis infections. For scabies, 24.4% (10/ 41) of dogs tested positive; of these, 80% (8/10, p≤0.05) had Demodex canis infections. In cats, 17.6% (3/17) were positive for dermatophytes; of these, 67% (2/3) were confirmed to have Microsporum gypseum infections. The positive testing rate for scabies in cats was 17.6% (3/17); of these, 67% (2/3) were Notoedres cati infections. In one cat, a concomitant infection was found witha dermatophyte (M. gypseum) and scabies (N. cati). It was concluded that the occurrence of dermatopathies is high at the SAMC/VH/IFPB. The main dermatophytes found were M. canis in dogs and M. gypseum in cats, and the most frequent scabies were D. canis in dogs and N. cati in cats.